Dishonorable Removal of a Notary for Breach of Professional Ethics: An Analysis of Decision No. 3/Pdt.G/2022/PN Plk - Waluya, Kintan Salma; Samosir, Tetti; Anggriani, Jum (Jurnal Ilmu Hukum Kyadiren, 2026)
Dishonorable dismissal of a notary constitutes the most severe administrative sanction, directly affecting the continuity of office and the professional legitimacy of notaries as public officials. This study examines the legality of dishonorable dismissal imposed on a notary for ethical violations and evaluates the role of the Regional Supervisory Council within the notarial oversight system, focusing on Decision Number 3/Pdt.G/2022/PN Plk. The research employs a normative legal method using statutory and case-based approaches. Primary and secondary legal materials are analyzed qualitatively through legal interpretation and juridical reasoning. The findings reveal that although the authority to dismiss notaries is normatively regulated under the Notary Office Act, its implementation in the case under study raises significant concerns regarding legal certainty, proportionality of sanctions, and compliance with procedural justice, particularly the right to defense. Furthermore, the Regional Supervisory Council has not functioned optimally as a professional guidance mechanism and tends to operate in a predominantly procedural-administrative manner. This study underscores the need to recalibrate the notarial supervision framework to ensure that dishonorable dismissal is imposed in an accountable, proportional, and legally reasoned manner consistent with the principles of good governance.